2022
DOI: 10.3389/fcell.2022.1042403
|View full text |Cite
|
Sign up to set email alerts
|

The guanine nucleotide exchange factor Vav3 intervenes in the migration pathway of oligodendrocyte precursor cells on tenascin-C

Abstract: Oligodendrocyte precursor cells (OPCs) are the exclusive source of myelination in the central nervous system (CNS). Prior to myelination, OPCs migrate to target areas and mature into myelinating oligodendrocytes. This process is underpinned by drastic changes of the cytoskeleton and partially driven by pathways involving small GTPases of the Rho subfamily. In general, the myelination process requires migration, proliferation and differentiation of OPCs. Presently, these processes are only partially understood.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 77 publications
(129 reference statements)
0
1
0
Order By: Relevance
“…Thereby, an adhesion repulsive effect of the alternatively spliced FnIII domains on OPCs are detected, while the migration of the cells is inhibited by the FnIII 78 domain ( Kiernan et al, 1996 ). It could be shown that the migration capability of OPCs on Tnc coating is dependent on the GEF Vav3 ( Schäfer et al, 2022 ). Furthermore, the maturation of OPCs is inhibited by Tnc substrate, as seen in a reduced myelin basic protein (MBP) expression which might be related to an interfering with Akt phosphorylation and contactin binding ( Czopka et al, 2009 , 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, an adhesion repulsive effect of the alternatively spliced FnIII domains on OPCs are detected, while the migration of the cells is inhibited by the FnIII 78 domain ( Kiernan et al, 1996 ). It could be shown that the migration capability of OPCs on Tnc coating is dependent on the GEF Vav3 ( Schäfer et al, 2022 ). Furthermore, the maturation of OPCs is inhibited by Tnc substrate, as seen in a reduced myelin basic protein (MBP) expression which might be related to an interfering with Akt phosphorylation and contactin binding ( Czopka et al, 2009 , 2010 ).…”
Section: Discussionmentioning
confidence: 99%